Percutaneus Transluminal Angioplasty Using Carbon Dioxide Contrast in Chronic Limb Threatening Ischemia patient with Renal Failure - Sabara, Saga Malela Aria; Adiarto, Suko (The Indonesian Heart Association, 2024)
Background: At the present times, it is estimated that more than 202 million patients suffer from peripheral arterial disease (PAD) worldwide. Chronic limb-threatening ischemia (CLTI) represents the end stage of PAD often need lower extremity amputation, and the aftermath can be worse. For the patient with CLTI and chronic renal disease (CKD) who need endovascular therapy, iodinated contrast may enhance the risk of contrast-induced nephropathy (CIN). CIN is an acute renal injury and may lead to irreversible loss of renal function. In high-risk patients who were allergic to iodinated contrast material and for those with renal insufficiency Hawkins in the 1970s pioneered the intra-arterial application of carbon dioxide (CO2) gas angiography to reduce the volume use of iodinated contrast. Case Illustration: Single case was presented in this report. An 80-years old man referred to National Cardiovascular Center Harapan Kita with the chief complaint of independent rest pain and non healing wound in his left forefinger, in accordance with the criteria CLTI. The duplex ultrasound examination shows total occlusion at left anterior tibialis artery. The patient then undergone percutaneous transluminal angioplasty (PTA) procedure using Carbon Dioxide (CO2) contrast agent and using Plain Old Balloon Angioplasty (POBA) technique for revascularization. The flow to the distal of left anterior tibialis artery returned using only 30 ml of Iodinated contrast. The follow up of this patient shows there is no increase of serum creatinine level and eGFR Summary: Endovascular therapy in patient with CLTI with high risk of operation could be performed in patient with CKD using the carbon dioxide contrast agent in order to minimize the usage of iodinated contrast avoiding further loss of renal function. In this case report, the procedure has performed successfully without increase in serum creatinine and decrease of GFR. Keywords: CLTI, Carbondioxide Contrast, Endovascular Therapy